2005
DOI: 10.1099/ijs.0.63310-0
|View full text |Cite
|
Sign up to set email alerts
|

Bacillus velezensis sp. nov., a surfactant-producing bacterium isolated from the river Vélez in Málaga, southern Spain

Abstract: Two Gram-positive, endospore-forming bacterial strains, CR-502T and CR-14b, which produce surfactant molecules are described. Phenotypic tests and phylogenetic analyses showed these strains to be members of the genus Bacillus and related to the species Bacillus atrophaeus, Bacillus mojavensis, Bacillus subtilis, Bacillus vallismortis and Bacillus amyloliquefaciens, although they differ from these species in a number of phenotypic characteristics. DNA–DNA hybridization confirmed that they show less than 20 % hy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
139
0
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 233 publications
(161 citation statements)
references
References 21 publications
(19 reference statements)
8
139
0
1
Order By: Relevance
“…The cell-wall peptidoglycan contained meso-diaminopimelic acid. The total cellular fatty acid profiles showed a large amount of branched fatty acids; the major components (>5.0 %) were anteiso-C 15 : 0 (34.8 %), iso-C 15 : 0 (21.9 %), iso-C 17 : 0 (15.7 %), anteiso-C 17 : 0 (11.4 %) and C 16 : 0 (9.7 %) ( the close relatives B. amyloliquefaciens, B. atrophaeus and B. velezensis determined in this study were consistent with previously reported profiles (Borriss et al, 2011;Nakamura, 1989;Ruiz-García et al, 2005). B. nakamurai could not be distinguished from its closest related species on the basis of fatty acid profiles.…”
supporting
confidence: 82%
“…The cell-wall peptidoglycan contained meso-diaminopimelic acid. The total cellular fatty acid profiles showed a large amount of branched fatty acids; the major components (>5.0 %) were anteiso-C 15 : 0 (34.8 %), iso-C 15 : 0 (21.9 %), iso-C 17 : 0 (15.7 %), anteiso-C 17 : 0 (11.4 %) and C 16 : 0 (9.7 %) ( the close relatives B. amyloliquefaciens, B. atrophaeus and B. velezensis determined in this study were consistent with previously reported profiles (Borriss et al, 2011;Nakamura, 1989;Ruiz-García et al, 2005). B. nakamurai could not be distinguished from its closest related species on the basis of fatty acid profiles.…”
supporting
confidence: 82%
“…DNA was extracted and purified from whole cells by the phenol method (Saito and Miura, 1963). 16S rRNA gene sequencing was carried out (Shida et al, 1996) by using the 27F and 1488R rRNA primers (Ruiz-Garcia, 2005). The five housekeeping genes were amplified using a set of primer as described by Juneja and Lazzaro (2009).…”
Section: Methodsmentioning
confidence: 99%
“…nov. was isolated during a research program to discover novel bacterial strains capable of synthesizing new lipopeptides with surfactant and/or antimicrobial activity. Genomic and phenotypic data demonstrated that B. velezensis is a novel species of Bacillus (Ruiz-García et al, 2005), now reclassified as B. amyloliquefaciens (Wang et al, 2008).…”
Section: Introductionmentioning
confidence: 99%